Effect of Adding NPK-Chitosan Fertilizer and Organic Matter on phosphorus and potassium content of Corn (Zea mays L.) - Basam Mazhar Kazem; Haifa Jassim Hussein; Abdullah Abbas Hussein (University of Thi-Qar Journal of agricultural research, 2024)
A field experiment was conducted at the College of Agriculture, University of Basrah's  research station in Garmat Ali during 2022 agricultural season. The study aimed to investigate the impact of three types of fertilizers (commercial NPK as a control and two types of prepared NPK-Chitosan organic fertilizers) at four addition levels (0, 1, 1.5, and 2 ton ha-1) and two levels of organic matter (0% and 2.5%) on the availability of nitrogen and potassium in loam sandy soil and yield of corn (Zea mays L.).The results indicated a significant effect of fertilizer type on increasing Phosphorus and Potassium Content of corn plant. The highest values of Phosphorus and Potassium Content for corn were 6.15 and 47.07 gm kg-1 respectively for the added fertilizer type. The NPK-Chitosan fertilizer in a 1:3 coating ratio achieved the, 3.62 and 31.01 kg ha-1, respectively, followed by the treatment of NPK-Chitosan fertilizer with a 1:3 mixing ratio and a fertilizer level of 2 tons/ha, which yielded The results showed a significant effect of fertilizer level on increasing Phosphorus and Potassium Content of the corn plants. Phosphorus and Potassium Content increased with higher levels of added fertilizer. The level 2 achieved the highest values of Phosphorus and Potassium Content for the vegetative part corn plants, reaching 2 tons per hectare.4.22 and 37.91 gm kg-1, and with a significant difference from level 1 and 1.5 tons per hectare, level 2 also outperformed level 0 tons per hectare (the control treatment). Similarly, the organic matter showed a significant effect the results indicated a significant interaction between the type and level of fertilizer, as well as the level of added organic matter to the soil, on Phosphorus and Potassium Content of the yellow corn plants. The NPK-Chitosan fertilizer with a 1:3 coating ratio added at the level of 2 tons per hectare outperformed the other treatments, yielding the highest phosphour contentand grain yield.